Accidental lead in contaminated pipe-borne water and dietary furan intake perturbs rats' hepatorenal function altering oxidative, inflammatory, and apoptotic balance - Solomon E. Owumi; Uche O. Arunsi; Omolola M. Oyewumi; Ahmad Altayyar (BMC, 2022)
Abstract Inadvertent exposure to furan and Pb is associated with hepatorenal abnormalities in humans and animals. It is perceived that these two chemical species may work in synergy to orchestrate liver and kidney damage. Against this background, we investigated the combined effect of furan and incremental lead (Pb) exposure on hepatorenal dysfunction. Wistar rats (n = 30; 150 g) were treated for 28 days accordingly: Control; FUR (8 mg/kg), PbAc (100 µg/L), FUR + PbAc1 (8 mg/kg FUR + 1 µg/L PbAc); FUR + PbAc1 (8 mg/kg FUR + 10 µg/L PbAc), and FUR + PbAc1 (8 mg/kg FUR + 100 µg/L PbAc). Biomarkers of hepatorenal function, oxidative stress, inflammation, DNA damage, and apoptosis were examined. Furan and incrementally Pb exposure increased the levels of hepatorenal biomarkers and oxidative and pro-inflammatory mediators, including lipid peroxidation, reactive oxygen and nitrogen species, and interleukin-1 beta. Increased DNA damage, caspases- 9 and -3, and atypical histoarchitecture of the hepatorenal tissues exemplified furan and Pb treatment-related perturbations. Furthermore, the levels of antioxidants and IL-10 were also suppressed. Furan and Pb dose-dependently exacerbated hepatorenal derangements by altering the redox and inflammatory rheostats, worsened DNA damage, and related apoptotic onset that may potentiate hepatorenal disorders in humans and animals. The findings validate the synergistic effect of furan and Pb in the pathophysiology of kidney and liver disorders.